Concurrent robot‐assisted radical prostatectomy and robot‐assisted partial nephrectomy for patients with synchronous prostate cancer and small renal tumor: A case series of five patients. Issue 3 (23rd March 2022) - Kanehira, Mitsugu; Tamura, Daichi; Matsuura, Tomohiko; Maekawa, Shigekatsu; Kato, Renpei; Kato, Yoichiro; Takata, Ryo; Obara, Wataru
Abstract: Robotic surgery has become widely used in the field of urology. We experienced concurrent robot‐assisted radical prostatectomy (RARP) and robot‐assisted partial nephrectomy (RAPN) for the complex cases of synchronous primary cancers. Concurrent RARP and RAPN with horseshoe kidney have not been reported to date. Mean operative time was 398.6 minutes and mean total console time was 259.6 minutes. Total mean estimated blood loss was 313.4 mL. None of the patients required conversion to open surgery, none needed blood transfusion, and no perioperative complications occurred. The mean estimated glomerular filtration rate at 1 month postoperatively was maintained compared to pre‐operative value. Positive surgical margin was shown in one patient with RARP. Concurrent RARP and RAPN using reusable ports can be safely performed. This combined surgery may be considered one of the treatment choices for synchronous prostate cancer and small renal tumor.